Life cycle analysis of renewable natural gas and lactic acid production from waste feedstocks. (15th August 2021) - Lee, Uisung; Bhatt, Arpit; Hawkins, Troy Robert; Tao, Ling; Benavides, Pahola Thathiana; Wang, Michael
Abstract: Producing fuels and chemicals from waste is considered economically favorable, due to low feedstock cost, and environmentally favorable, due to avoided emissions from conventional waste management practices. In this study, we evaluate the life cycle greenhouse gas (GHG) emission reduction benefits of renewable natural gas (RNG) and lactic acid (LA) production from four types of wet waste feedstocks (wastewater sludge, food waste, swine manure, and fats, oil, and grease [FOG]) via anaerobic digestion (AD) and LA fermentation, respectively. RNG can be used as an alternative to fossil natural gas, while LA from waste feedstocks can displace conventional LA production pathways (mainly from corn via fermentation). Providing comprehensive life cycle GHG emissions of the combinations of waste feedstocks and products through different routes helps identify the GHG hotspots and show where emissions savings come from. The results show that the carbon intensities (CIs) of waste-derived RNG and LA are much lower than those of their counterparts. We estimated the life cycle GHG emissions for RNG to be between −146 and 27 g carbon dioxide equivalent (CO2 e)/MJ, much lower than the CI of fossil fuels. Waste-derived LA pathways also show substantially lower CIs, ranging from −4.2 to −1.4 kgCO2 e/kg LA, compared to the CIs of LA from corn and corn stover (1.2 and 0.3 kgCO2 e/kg LA, respectively). We will also discuss that the low CIs of waste-derived products can come from low yields leading to high emission credits. Thus, life cycle analysis results presented per weight of treated waste can be used to support decisions about which waste feedstocks and products are to be used for sustainable waste valorization. In addition, we found that monetary emission reduction credits can play an important role in driving waste valorization. Graphical abstract: The Images of Waste, Trash Can, Flame, Beaker, and Sewer in the Graphical Abstract Are Public Domain, Courtesy of the Noun Project. Image 1 Highlights: Renewable natural gas and lactic acid can be produced from organic waste materials. Conducted LCA to quantify the environmental benefits of waste-derived products. Producing fuels/chemicals from waste can reduce GHG emissions. Quantified potential economic benefits led by GHG emission reductions. Economic benefits by GHG emission reductions can drive waste valorization.